2019
DOI: 10.3390/ijerph16122110
|View full text |Cite
|
Sign up to set email alerts
|

The Gambling Factors Related with the Level of Adolescent Problem Gambler

Abstract: The purpose of this study was to investigate the gambling factors related with the gambling problem level of adolescents to provide basic information for the prevention of adolescent gambling problems. The data was drawn from the 2015 Survey on Youth Gambling Problems of the Korea Center on Gambling Problems for Korean students in grades 7–11 (ages 13–17 years) and included 14,011 study subjects (average age 14.9 years, 52.5% male). The lifetime gambling behavior experience was 42.1%, and 24.2% had a gambling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 27 publications
0
30
0
3
Order By: Relevance
“…Most studies observed whether young people had ever participated in gambling or had gambled within the previous 12 months, and reported the prevalence of problem gambling, which was typically reported as low or moderate risk of problem gambling, or problem gambling. Lifetime participation in gambling rates ranged between 42.1% [10] and 89.9% [20], with the majority of studies that examined gambling participation reporting that around a third or more of adolescents or young adults confirmed that they had gambled at least once in their lifetime [10,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Gambling participation rates during the past 12 months ranged between 18.6% [38] to 85% [23].…”
Section: Gambling Participation and Problem Gamblingmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies observed whether young people had ever participated in gambling or had gambled within the previous 12 months, and reported the prevalence of problem gambling, which was typically reported as low or moderate risk of problem gambling, or problem gambling. Lifetime participation in gambling rates ranged between 42.1% [10] and 89.9% [20], with the majority of studies that examined gambling participation reporting that around a third or more of adolescents or young adults confirmed that they had gambled at least once in their lifetime [10,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Gambling participation rates during the past 12 months ranged between 18.6% [38] to 85% [23].…”
Section: Gambling Participation and Problem Gamblingmentioning
confidence: 99%
“…Adolescent problem gambling can lead to many complex problems, such as criminal behaviour, poor academic achievement, school truancy, financial problems, depressive symptoms, suicide, low self-esteem, deterioration of social relationships, and substance abuse [10]. More than two thirds of adult gamblers have reported that exposure to gambling during adolescence was a key contributing factor to their current gambling [11], indicating that preventive measures taken to reduce gambling during adolescent years could potentially reduce the prevalence of problem gambling in the adult population.…”
Section: Introductionmentioning
confidence: 99%
“…The NGCC controls the number of gambling businesses in the country as well as media content so that advertising is not released that may inspire excessive gambling. Limited gambling activities are legal and accessible for Koreans older than 18 years of age, as Korean citizens are only allowed to gamble in one of its casinos and participate in legal sports betting or lotteries [ 72 , 73 ].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, the prevalence of problem gambling ranges from 0 to 6%, and despite some differences in prevalence rates, findings across countries are quite consistent [1]. Recent findings show that gambling problems are particularly high among young people in Spain [49][50], whereas the United States, South Korea, and Finland are somewhat more analogous in their youth problemgambling prevalence rates [1,[51][52].…”
Section: Evidence On Problem Gambling In Different Spheresmentioning
confidence: 99%